2011
DOI: 10.1590/s0004-27302011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor cerebri during Cushing's disease treatment with ketoconazole

Abstract: SUMMARYBenign intracranial hypertension (Pseudotumor cerebri) has been described as related to the reduction in steroid levels in Cushing's disease (CD), especially after surgical remission. Ketoconazole is a common and effective adjuvant therapy for hypercortisolism, but the major concern is liver enzyme dysfunction. We describe here the case of a 12-year old girl with CD who developed benign intracranial hypertension during treatment with ketoconazole. She presented headache, vomiting, a black spot on her ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Therefore, we believe that the true cause of pseudotumor in our patients may have been glucocorticoid tapering, since all patients were receiving this medication in progressively smaller doses. Case reports of patients with Cushing's syndrome have shown that treating hypercortisolism with drugs such as ketoconazole could trigger pseudotumor cerebri 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we believe that the true cause of pseudotumor in our patients may have been glucocorticoid tapering, since all patients were receiving this medication in progressively smaller doses. Case reports of patients with Cushing's syndrome have shown that treating hypercortisolism with drugs such as ketoconazole could trigger pseudotumor cerebri 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Ketoconazole, which blocks adrenal steroidogenesis and lowers cortisol levels, has also been reported to cause IIH. 15 As initial symptoms can also be confused with AI in both children or adults, 9 the exact prevalence of mild IHH in patients treated with adrenal steroidogenesis inhibitors is not known. Retinoic acid, which has the potential to decrease ACTH and cortisol in some patients, has also been described to induce IIH in patients with chronic lymphocytic leukemia (CLL).…”
Section: Discussionmentioning
confidence: 99%
“…One female patient developed pseudotumor cerebri syndrome, which was treated with acetazolamide. She did not need to discontinue ketoconazole, having used it for more than 10 years without new side effects and achieving complete control of hypercortisolism (24). Another patient became pregnant during follow-up while using the medication, but no maternal or fetal complications occurred (25).…”
Section: Side Effectsmentioning
confidence: 99%